Effectiveness of Podcasts to Improve Students Listening Comprehension for Vocational Students - Tunarsih, Asih; Sulistianingsih, Endang; Jamaludin, Sanday (Journal of Management, Education and Communication, 2025)
The purpose of this study was to find out the effectiveness of podcasts in improving listening skills. The approach used in this study was quantitative. This type of research is a true experiment. The research design is a pretest-posttest control group design. This study's population consisted of all students in class XI who were taught by the same teacher. Samples were taken using the cluster random sampling technique by taking two classes, namely the experimental class, and the control class. The data was collected using test and questionnaire techniques. The data were analyzed using an independent sample t-test. The result indicated that podcasts were effective to improve students’ listening skills. The study suggests that instructional design that utilizing podcasts should well prepared